Genomics of neurodevelopmental disorders - Mendez-Rosado, Luis Alberto; Lantigua Cruz, Aracelis Lantigua Cruz; Zelenova, Maria Zelenova; Vorsanova, Svetlana; Iourov, Ivan (Revista Cubana de Pediatría, 2020)
Introduction: Neurodevelopmental disorders (NDD) are featured by a delay in the acquisition of motor functions, cognitive abilities and speech, or combined deficits in these areas with the onset before the age of 5 years. Genetic causes account for approximately a half of all NDD cases. Objective: to describe alterations of the genome implied in neurodevelopmental disorders and some aspects of their genetic counseling. Methods: Bibliographic search in Medline, Pubmed, Scielo, LILACS and Cochrane, emphasizing in the last five years, the relationship between the various genetic factors that may be involved in neurodevelopmental disorders. Results: Multiple genetic factors are involved in neurodevelopmental disorders, from gross ones such as chromosomal aneuploidies to more subtle ones such as variations in the number of copies in the genome. Special emphasis is placed on microdeletion-micro duplication syndromes as a relatively frequent cause of NDDs and their probable mechanisms of formation are explained. Final Considerations: Genetic aberrations are found in at least 30-50% of children with NDD. Conventional karyotyping allows the detection of chromosomal aberrations encompassing more than 5-7 Mb, which represent 5-10% of causative genome rearrangements in NDD. Molecular karyotyping (e.g. SNP array/array CGH) can significantly improve the yield in patients with NDD and congenital malformations. Keywords: CNV; chromosomal abnormalities; genome; genomic aberrations; microdeletions; microduplications; neurodevelopmental disorders.